THE EFFECT OF USING FLASHCARDS ON STUDENT VOCABULARY MASTERY - Riryn Fatmawaty (Reforma : Jurnal Pendidikan dan Pembelajaran, 2016)
As we know that vocabulary is as a major component of language learning. Without having adequate vocabulary we will get difficulty to learn English. So that way it has to be mastered by learners. It should be the first priority in English language teaching and learning because as a central of language teaching and learning. It means that by mastering vocabulary, of course with grammar, the learners will produce so many sentences easily either in spoken or written one. Actually, there are many methods that used by teacher in English's teaching in order to reach the goal in teaching and learning English, such as using cartoon movies, pictures, jigsaws, games, song and etc. Another way is learning through vocabulary card or flashcard. As we listen and read, we often meet new words by flashcard. A flashcard is a set of cards bearing information, as words or numbers, on either or both sides, used in classroom drills or in private study". The problem of the study is the students vocabulary mastery of MI. Babul Ulum Dorogede Gedangan Sukodadi Lamongan is very low, so researcher does a research in that school in a month, there are two meetings for doing pre test and post test, while four time for teaching and learning activities for each class by using flashcard. In doing research, the experimental class were given several treatments, while the control group get the lesson as usual. The topics lessons, teacher, pre-test and post test were same, but the method of teaching was different. Based on the result of statistic test, it is known that the result scores of experiment class is higher than control class and it is described as follows; based on the normality test, that the result from experiment class is (-2,7756 < 11,3449), and from control class is (-19,6799 < 11,3449). That means H0 received, both samples is from population distributes normal. Based on the homogeneity test is (2,25 < 3,69), that H0 us received. So that, both samples is from variant homogeneity. Based on the differences between mean with the t-test, that is (2,12 < 6,69), means that H0 is refused. So, the final score of students who taught by using flashcard is better than the students who do not use.Keywords: Flashcard, Vocabulary mastery